The development of tourism and its relationship with foreign languages: the case of Antioquia (Colombia) (2023)
In this article we report partial results of a needs assessment on language issues (foreign and native) in various sectors in Antioquia, Colombia, particularly regarding the tourism sector. Although the study does not focus on this sector specifically, the data revealed the growing importance of tourism in the department and the role of foreign languages in its strengthening. In this diagnosis, a document analysis of municipal development plans, a survey, focus groups, and interviews with different actors from the educational, productive, governmental and civil society sectors were carried out. The findings reflect the relevance of tourism in the social and economic development of the regions, as well as the growing importance of foreign languages, especially English, in the provision of tourist services and its close relationship with the vocation of the territories.